A marca Instituto Evandro Chagas e a Amazônia enquanto território produtor de ciência - BASTOS, Fábio Augusto Silva (Universidade Federal do Pará, 2023)
This study analyzes the brand discourse of the Instituto Evandro Chagas (IEC) considered one of the most important research institutions in the North region founded in 1936, to understand how this discourse presents the Amazon region as a territory that produces science. Four institutional disclosure documents of the IEC from 1990 to 2021 and semi-structured interviews with researchers from the institution were used as research corpus, in addition to documents referring to the history of the Institute. This is an exploratory qualitative research, as a methodology for brand analysis, it uses a multiperspective approach (BONIN, 2008) with brand concepts and project/manifestations model proposed by Semprini (2010) together with the theory of social discourses, media discourse analysis, and reading contract of Verón (1983; 1986; 1987; 2004). As a theoretical view to observe the investments in the brand's meaning, the concept of the Amazon Brand (AMARAL, 2011, 2015, 2016) is used with other authors who analyze the Amazon region, its history, imagery, and symbolic constructions (COSTA, 2017; DUTRA, 2003; GONDIM, 2007; LOUREIRO, 2022). Decolonial theories (QUIJANO, 1993; MIGNOLO, 2003, 2017) and abyssal thinking (BOAVENTURA, 2009) are also used as an epistemological basis for a critical point of view about symbolic constructions of the hegemonic model of science as a way of legitimizing Eurocentric superiority and as a factor of geopolitical hierarchization in the production of knowledge. As a result, there is an ambiguous condition: it appears that the Amazon region is discredited and peripheral when the local production of science is in focus, but at the same time, it retains a high degree of visibility in the production of science in/ and about the Amazon.